2021
DOI: 10.1136/jitc-2021-002787
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 induces immunosuppression via CD48 on regulatory T cells in hepatocellular carcinoma

Abstract: BackgroundA better understanding of the molecular mechanisms that manifest in the immunosuppressive tumor microenvironment (TME) is crucial for developing more efficacious immunotherapies for hepatocellular carcinoma (HCC), which has a poor response to current immunotherapies. Regulatory T (Treg) cells are key mediators of HCC-associated immunosuppression. We investigated the selective mechanism exploited by HCC that lead to Treg cells expansion and to find more efficacious immunotherapies.MethodsWe used match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 49 publications
(68 reference statements)
0
48
0
Order By: Relevance
“…Candidate receptors for GDF-15 are ALK-5/TGF-bRII, TGF-bRI, TGF-bRII and the epithelial growth factor receptor ErbB2 (35)(36)(37). Recently, a new receptor for GDF-15, CD48, has been identified on Treg cells in a genetically-engineered mouse model (38). The GDF-15-CD48 interaction was shown to promote the propagation of Treg cells and indirectly upregulate forkhead transcription factor (Foxp3), enhancing the development of hepatocellular carcinoma (HCC) (38).…”
Section: Cellular Mechanisms and Downstream Signaling Pathways Of Gdf-15mentioning
confidence: 99%
See 2 more Smart Citations
“…Candidate receptors for GDF-15 are ALK-5/TGF-bRII, TGF-bRI, TGF-bRII and the epithelial growth factor receptor ErbB2 (35)(36)(37). Recently, a new receptor for GDF-15, CD48, has been identified on Treg cells in a genetically-engineered mouse model (38). The GDF-15-CD48 interaction was shown to promote the propagation of Treg cells and indirectly upregulate forkhead transcription factor (Foxp3), enhancing the development of hepatocellular carcinoma (HCC) (38).…”
Section: Cellular Mechanisms and Downstream Signaling Pathways Of Gdf-15mentioning
confidence: 99%
“…The GDF-15-CD48 interaction was shown to promote the propagation of Treg cells and indirectly upregulate forkhead transcription factor (Foxp3), enhancing the development of hepatocellular carcinoma (HCC) (38). This immunosuppressive tumor microenvironment was further shown to be altered by the introduction of monoclonal antibodies against GDF-15, which ultimately improved HCC control (38). Downstream signaling of GDF-15 has been studied in different models.…”
Section: Cellular Mechanisms and Downstream Signaling Pathways Of Gdf-15mentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Recently, CD48 is the rst discovered receptor of GDF15 in the immune system and is exclusively expressed on immune cells. 21 In co-culture experiment we looked for the uptake of rCPCs derived GDF15 by CD48 receptor on T-cells by ow. Data showed that all CD4 cells has CD48 receptor and the uptake of GDF15 by T-cells was signi cantly higher in rCPCs group as compared to control and rCPC-GDF15KD cells (Fig.…”
Section: Role Of Gdf15 In the Effects Of Rcpcs On LV Functional Recoverymentioning
confidence: 99%
“…We have shown previously that CPCs secrete Growth Differentiation Factor 15 (GDF15) 8 , a cytokine produced in response to mitochondrial stress thought to contribute to adaptive homeostatic changes in response to tissue damage 16 . GDF15 has also peripheral anti-in ammatory/immunomodulatory and cardioprotective effects [17][18][19][20][21] . We hypothesized that transplanted allogeneic CPCs are immunomodulatory and exert cardioprotective effects similar to those observed with autologous CPCs.…”
Section: Introductionmentioning
confidence: 99%